MODEL PENDIDIKAN AKHLAK DI SEKOLAH Sebuah Model Pengembangan Suasana Religius di Sekolah - Wahyudin Wahyudin (Madania: Jurnal Ilmu-Ilmu Keislaman, 2012)
The decline of public attention towards school is marked by the declining interest of parents to send their children to conventional schools. Therefore, educational policies should emphasize that religious atmosphere needs to be developed at schools. The development can be done through the implementation of polite way of dressing, neat and genitally covered, reciting al- Qur'an, exemplary of teachers are among other things that religion is highly recommended. This appearance should be implemented both outside and inside the classroom.